THE EFFECT OF DISTRACTION TECHNIQUES ON ANXIETY LEVELS IN PREGNANT WOMEN ABOUT THE PROCESS OF LABOR IN WONOGIRI - Putri Halimu Husna; Retno Dwi Puji Astuti (Jurnal Keperawatan GSH, 2018)
Latar Belakang : Kecemasan adalah kondisi emosi dan pengalaman subjektif individu terhadap objek yang tidak jelas dan spesifik akibat antisipasi bahaya yang memungkinkan individu melakukan tindakan untuk menghadapi ancaman. Kecemasan pada ibu hamil sangatlah beresiko karena bisa mengakibatkan kematian pada ibu dan janin. Teknik distraksi diharapkan daapat menurunkan tingkat kecemasan dari ibu hamil.Tujuan : Tujuan penelitian ini adalah menurunkan tingkat kecemasan pada ibu hamil yang menghadapi proses persalinan.Metode Penelitian :Penelitian ini merupakan penelitian kualitatif dengan pendekatan case study research (studi kasus). Dengan jumlah responden 3 ibu hamil dengan usia kehamilan trimester 3. Teknik sampling menggunakan teknik cluster random sampling. Pengumpulan data dengan menggunakan wawancara, observasi, dan mengukur tingkat kecemasan sebelum dan sesudah pemberian teknik distraksi. Instrumen yang digunakan dalam studi ini adalah kuesioner Hamilton Anxiety Rating Scale (HARS).Hasil : Hasil studi menunjukkan menunjukkan tingkat kecemasan informan sebelum perlakuan yaitu informan 1 dengan skor 21, informan 2 dengan skor 21, informan 3 dengan skor 25. Tingkat kecemasan informan setelah perlakuan yaitu informan 1 dengan skor 13, informan 2 dengan skor 12, informan 3 dengan skor 13.Kesimpulan Kesimpulan studi ini menunjukkan tingkat kecemasan ketiga responden teratasi dengam teknik distraksi, ada penurunan tingkat kecemasan setelah pemberian teknik distraksi. Background: Anxiety was a condition of emotions and subjective experiences of individuals towards objects that were not clear and specific due to the anticipation of danger which allows individuals to take action to face threats. Anxiety in pregnant women was very risky because it could cause death to both the mother and the fetus. The distraction technique was expected to reduce the anxiety level of pregnant women.Purpose: The purpose of this study was to reduce the level of anxiety in pregnant women who are facing childbirth.Methods: This research used a qualitative study with a case study research approach. The number of respondents was 3 pregnant women with 3rd trimester of pregnancy. The sampling technique used a cluster random sampling technique. Collecting data using interviews, observation, and measuring the level of anxiety before and after giving distraction techniques. The instrument used in this study was the Hamilton Anxiety Rating Scale (HARS) questionnaire.Results: The results of the study showed that the level of anxiety of the informants before the treatment was informant 1 with a score of 21, informant 2 with a score of 21, informant 3 with a score of 25. The level of anxiety of the informants after the treatment was informant 1 with a score of 13, informant 2 with a score of 12, informant 3 with a score of 13. Conclusion: The conclusion of this study shows that the anxiety level of the three respondents is resolved by the distraction technique, there is a decrease in the level of anxiety after giving the distraction technique.